Dolce vita podróżnika, czyli o miłości i wierności słów kilka - Wiszowata, Magdalena (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2013)
The problem of the fidelity of a pair of major heroes, and their many travels and their resultant constant vicissitudes, is one of the main plot-threads used by authors of extant ancient romances, as selected by me; namely the Tales of Xenophon of Ephesus (1st/2nd century), Daphnis and Chloe by Longus (2nd century), Tales of Leucippe and Clitophon by Achilles Tatius (2nd/3rd century) and the Aethiopica (Theagenes and Chariklea) of Heliodorus (3rd/4th century).
Keywords: ancient Greek novel or romance; Xenophon of Ephesus; Longus; Achilleus Tatius; Heliodorus